2012
DOI: 10.3724/sp.j.1263.2012.01101
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin intoxication: An old enemy in modern era

Abstract: ObjectivesAlthough development of new treatment modalities limited digoxin usage, digoxin intoxication is still an important issue which could be easily overlooked. In this report, we analyzed a case series definitively diagnosed as digoxin intoxication in the modern era.MethodsWe analyzed 71 patients hospitalized with digoxin intoxication confirmed by history, complaints, clinical and electrocardiograph (ECG) findings, and serum digoxin levels > 2.0 ng/mL, during a five year period. The demographic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
14
1
3
Order By: Relevance
“…The rate of death was 7%; meanwhile, based on the results of the present study, it was noticed that the mortality rate was 4.9% lower than the study by Kirilmaz. The majority of deaths were in the recent study due to cardiac complications (5). Furthermore, Aarnoudse et al reported a lower mortality rate (0.7%) compared to that in this study (12).…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…The rate of death was 7%; meanwhile, based on the results of the present study, it was noticed that the mortality rate was 4.9% lower than the study by Kirilmaz. The majority of deaths were in the recent study due to cardiac complications (5). Furthermore, Aarnoudse et al reported a lower mortality rate (0.7%) compared to that in this study (12).…”
Section: Discussioncontrasting
confidence: 42%
“…Higher age and potassium levels above normal range were the factors that independently predicted poor prognosis in the patients. In a study carried out by Kirilmaz et al (2012), 71 patients with digoxin poisoning were investigated. In this study, 5-year time series has been selected for sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As therapeutic and toxic dosages of cardiac glycosides are almost identical, drug toxicity is common (2). Digoxin toxicity effects different parts of the body, such as the central nervous system with many side effects, such as headache, fatigue, dizziness and visual disturbances, digestive system such as nausea, vomiting, anorexia, and the cardiovascular system, such as arrhythmia (3)(4)(5). These side effects could be more dangerous in the elderly as their recuperative abilities may be inadequate as a result of numerous factors, including impaired hepatic or renal function as well as chronic disease processes (6).…”
Section: Introductionmentioning
confidence: 99%